Measures aiding in identifying voluntarily helpful employees: an accounting student sample. Issue 5 (28th August 2018) - Lyons, Paul; Bandura, Randall P.
Abstract : Purpose: There have been few attempts to identify valid and efficient self-assessment measures for use by human resource practitioners or line managers to help distinguish job applicants and/or employees who may have a predisposition to offer voluntary helpful behavior, or contextual performance, on the job. This paper (exploratory and correlational) aims to identify measures that are positively and highly related to this valuable work behavior. Findings set the stage for further study and research aimed at creating predictive measures that possess reliable statistical properties. Design/methodology/approach: Study design has two components: first, identity and analysis of measures of performance that are broadly supported in research literature; and second, correlational analysis of contextual performance measures with critical self-assessments. No effort to discover cause and effect linkages is reported; only relationships are disclosed. Findings: Of the self-assessments examined, two (core self-evaluation and self-efficacy) were found to be positively and significantly related to valid measures of voluntary, helpful organizational behavior, in this case, measures of contextual performance and job dedication. Research limitations/implications: The study made no attempt to establish statistically valid predictors of behavior. Sample size was relatively small and consisted of students preparing for a career in accounting. Originality/value: Voluntary, helpful employee behavior is valuable in virtually all organizations. Isolated here are two brief and easy-to-administer self-assessments which may assist in the identification of individuals who possess an inclination to offer such behavior.